2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346287
|View full text |Cite
|
Sign up to set email alerts
|

IPSIHAND BRAVO: An improved EEG-based brain-computer interface for hand motor control rehabilitation

Abstract: Stroke and other nervous system injuries can damage or destroy hand motor control and greatly upset daily activities. Brain computer interfaces (BCIs) represent an emerging technology that can bypass damaged nerves to restore basic motor function and provide more effective rehabilitation. A wireless BCI system was implemented to realize these goals using electroencephalographic brain signals, machine learning techniques, and a custom designed orthosis. The IpsiHand Bravo BCI system is designed to reach a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…In that study, EEG signals from the unaffected hemisphere could be used for successful BCI control. In addition, the same group developed a brain-controlled hand orthosis for motor recovery using neural activities from the ipsilesional hemisphere (Holmes et al, 2012 ). Hence, signals from the contralesional hemisphere may serve as an alternative neural pathway for BCI control.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, EEG signals from the unaffected hemisphere could be used for successful BCI control. In addition, the same group developed a brain-controlled hand orthosis for motor recovery using neural activities from the ipsilesional hemisphere (Holmes et al, 2012 ). Hence, signals from the contralesional hemisphere may serve as an alternative neural pathway for BCI control.…”
Section: Discussionmentioning
confidence: 99%
“…A final sample of 30 studies were included in the qualitative review. Among the 30 studies, 11 [75][76][77][78][79][80][81][82][83][84][85] were involved in testing the BCI-hand robot system on chronic and subacute stroke patients ( [75,80] are RCTs) while the rest involved testing on healthy participants [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]. Table 2 shows a summary of the relevant data fields extracted from these studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…The studies in this review included single-finger [84][85][86], multi-finger [82] (including EMOHEX [78,79,87]), full hand gloves [88,89] (including mano: Hand Exoskeleton [90] and Gloreha [91]) and full arm exoskeletons with isolated finger actuation (BRAVO-Hand [76]). Nine of the studies [77,87,88,90,[92][93][94][95][96] presented their novel design of a hand rehabilitation device within the article while some reported on devices reported elsewhere (i.e., in a previous study of the group or a research collaborator). Two commercially-available devices were also used: AMADEO (Tyromotion, Austria) is an end-effector device used in 3 studies [97][98][99], and Gloreha (Idrogenet, Italy) is a full robotic hand glove used by Tacchino et al [91].…”
Section: Robot-assisted Rehabilitationmentioning
confidence: 99%
“…In order to facilitate hand MI and account for significant time-points in the EEG data, all the studies employed a cue-feedback strategy during their trials. 19 of the studies presented a form of visual cue while the rest, except for two unspecified [69,87], involved cues in auditory ("bleep") [76,[80][81][82][83], textual [78,79,89] or verbal [88] forms. As for the provision of a matching sensory feedback, 16 studies presented a combination of kinaesthetic and visual feedback with some also providing auditory feedback during successful movement attempts.…”
Section: Discussionmentioning
confidence: 99%
“…A final list with 30 studies was identified as eligible for qualitative review. Among the 30 studies, 11 [60][61][62][63][64][65][66][67][68][69][70] were involved in testing the BCI-hand robot system on chronic and subacute stroke patients ( [60,65] are RCTs) while the rest involved testing on healthy participants [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Figure 1 Study Selection Flowchartmentioning
confidence: 99%